COVID-19 induced renal injury differs from that in other viral-infections. Issue 1 (7th March 2022) - Parise, Rachel S.; Govindarajulu, Manoj; Ramesh, Sindhu; Thomas, Tony; Moore, Timothy; Dhanasekaran, Muralikrishnan
Abstract: Background: Kidney injuries caused by several viral diseases have been reported worldwide among all age groups, races, and genders. Of particular importance is coronavirus disease 2019 (COVID-19), and its prevalence in communities infecting all patient populations with symptoms ranging from asymptomatic to severe, including complications and mortality. Methods: Data were acquired from PubMed, Scopus, Google Scholar, Centers for Disease Prevention and Control (CDC), and Lexi-Comp using the following search terms: "COVID-19 and renal pathology, " "COVID-19 induced kidney disease, " "Viral infection induced kidney disease, " and "Viral infection induced renal damage." Titles and abstracts were manually analyzed as per the exclusion and inclusion criteria of relevant articles; relevance of articles included studies on the pathology of a specific viral infection and the impact of the virus on the adult renal system. Results: The mechanisms for renal disease due to COVID-19 include direct renal tubular injury, cytokine storm, inflammation, thrombosis vs. acute tubular necrosis, thrombotic events, and direct renal injury. Although some mechanisms behind renal dysfunction among the studied viral infections are similar, the prevalence rates of kidney injury or damage differ. This might be described by recommended prophylactic and therapeutic approaches that can alter the viral infection characteristics and possibly the impact a particular organ system. Conclusion: The patient population at risk was old in age and had a high body mass index. The mechanisms associated with renal dysfunction are similar, including direct renal injury through angiotensin converting enzyme 2 (ACE2) entry, inflammation, and thrombosis. The renal pathology of coronaviruses that differs from that of other prevalent viral infections is the activation of cytokine storm, which causes elevations of a greater number and different kinds of cytokines than other viral infections.